Experimental characterization and analytical modelling of the mechanical behaviour of fused deposition processed parts made of ABS-M30 - Croccolo, Dario; De Agostinis, Massimiliano; Olmi, Giorgio (Computational materials science, 2013)
•Mechanical properties of Fused Deposition Modelling (FDM) components depending on process parameters.•Effects generated by the contouring on the tensile strength and on the stiffness of FDM components.•Closed-form analytical model for the prediction of the mechanical properties of FDM components.•Validation of the model by comparison to experimental data. The Fused Deposition Modelling process is a highly efficient Rapid Prototyping approach that makes it possible to rapidly generate even much complicated parts. Unfortunately, the Fused Deposition Modelling is affected by several parameters, whose setting may have a strong impact on the components strength. This paper is devoted to the study of the effects generated by the Fused Deposition Modelling production parameters on the tensile strength and on the stiffness of the generated components, tackling the question from both the experimental and the numerical points of view. For this purpose, an analytical model was developed, which is able to predict the strength and the stiffness properties, based on the number of contours deposited around the component edge and on the setting of the other main parameters of the deposition process. The fundamental result of the paper consists in the possibility of predicting the mechanical behaviour of the Fused Deposition modelled parts, once the raster pattern (dimensions, number of contours, raster angle) has been stated. The effectiveness of the theoretical model has been verified by comparison to a significant number of experimental results, with mean errors of about 4%.